PENGELUARAN ROKOK RUMAH PADA RUMAH TANGGA YANG MENGKONSUMSINYA - Rizka Ayu Oktaviani; Nurcholis Nurcholis; Fadjar Suhaeri (Jurnal Ekonomi dan Bisnis, 2022)
The role of food commodities on the poverty line is much greater than the role of non-food commodities (housing, clothing, education, and health). Filter kretek cigarettes make the second-largest contribution to the poverty line. In addition, various scientific evidence state that smoking is a risk factor that causes morbidity and mortality from non-communicable diseases such as coronary heart disease, hypertension, stroke, respiratory disorders and cancer, impotence, pregnancy, and fetal disorders. Therefore, this study aims to determine the factors that influence the expenditure on cigarettes in households that consume them. The share of expenditure on cigarette consumption shows a different value in each quintile, so quantile regression is used in this study to see the influence of these factors at various quantile levels. The results of this study indicate that the education level of the head of household in the higher education category, the average per capita expenditure, the age of the head of the household, and the occupation sector of the head of the household have a significant effect on household spending on cigarette consumption at various quantile levels. Meanwhile, the variable that gives a bigger effect as cigarette consumption increases is the average per capita expenditure.